Fishery and population dynamics of Protonibea diacanthus (Lacepede) and Otolithoides biauritus (Cantor) landed by trawlers at Vanakbara, Diu along the west coast of India - Ghosh, Shubhadeep; Mohanraj, G; Asokan, P K; Dhokia, H K; Zala, M S; Bhint, H M; Suker, Anjani (Indian Journal of Fisheries, 2016)
The fishery and population characteristics of larger sciaenids Protonibea diacanthus (Lacepede) and Otolithoides biauritus(Cantor) landed by trawlers at Vanakbara, Diu were studied for the period 2003 – 2007. The average annual catch ofP. diacanthus was 770.6 t and that of O. biauritus was 1018.6 t, together contributing 12% to the total trawl catch at Vanakbara.Majority of the larger sciaenids were landed during September - December. The von Bertalanffy growth equation wasLt = 145.3 [1 – e - 0.14 (t + 0.0738)] for P. diacanthus and Lt = 160 [1 – e - 0.19 (t + 0.0638)] for O. biauritus. The mortality rates M, F andZ computed for P. diacanthus were 1, 0.30 and 0.61 and for O. biauritus were 7, 0.33 and 0.70. The exploitation ratio (E) was0.49 for P. diacanthus and 0.47 for O. biauritus. A maximum increase in relative yield by 2.7% for P. diacanthus could berealized by decreasing the present level of fishing by 20%, while for O. biauritus the present fishing effort is at optimumlevel.